Crural recurrences in inguinal herniorrhaphy - Croci, Fabio; Pérez Penco, Ernesto; Tarabochia, Carlos; Olivieri, Lucy (Cirugía del Uruguay, 1986)
Crural recldivation In inguinal herniorrhaphy Is a well known pathology though no clearly deflned. lt has an approximate frequency rate of 3% over total recidivatlon cases. lt must be taken into account that between a 20 and a 40 percent of crural recldlvations recognize as their antecedent a previous inguinal repalr. They may appear after any Inguinal repair procedure and, to be classified as such, must comply with chronological and pathological requlrements deflnlng same. Their repairing will vary according to the Inguinal herniorrhaphy previously carried out.